Pedagogical action of nursing at school: learning, reflecting and acting in the prevention of dengue - Fabiano Pereira dos Santos; Priscila da Silva Matter; Adriane Cristina Bernat Kolankiewicz (Universidade Federal de Santa Maria, 2017)
Aim: to describe the experience of intersectoral action in primary care with nursing students. Method: experience report, from the development of activities at school, with the participation of 153 students, in March 2016. Results: the students were stimulated to develop actions to control and prevent the dissemination of the Aedes Aegypti mosquito, by means of intersectoral thinking among institutions located in the same community, enlightened by the School Health Program. Final considerations: the development of conjoined strategies and alignments of actions in intersectoral organization promotes convergent interventions for community improvements. Accordingly, the intertwined work entails growth in health, society and politics, with preventive intent promotion of health in an inclusive way, discussed by several institutional actors